Solid waste management in the rural community Boca da Mata - Jardim-CE (Research, Society and Development, 2021)
One of the main concerns linked to sustainability concerns the exacerbated generation of solid waste, in view of the environmental and, therefore, social and economic impacts caused by their inadequate disposal, especially in rural areas, where the management of solid waste in these homes is still incipient in Brazil. In this perspective, this article aims to assess the destination of solid waste in the Boca da Mata- Jardim-CE community. The specific objectives are: to present the socioeconomic profile of the residents of the Boca da Mata Community, to analyze the disposal of solid waste in that location, as well as to present the perception of residents in relation to the socio-environmental harm caused by the environmentally inadequate disposal and to hold lectures on alternatives to the management and handling of household solid waste. Thus, a quali-quantitative research was carried out through a semi-structured questionnaire. Considering the results, it was identified the occurrence of solid waste collection service, however, residents are responsible for the destination of the generated waste, since 90% of respondents burn their waste. It is noteworthy that as a result of the lack of education, considering that the majority (42%) of respondents have incomplete primary education, or even cultural influences, as 69.4% of respondents claimed to know the harms of such in this action, residents still dispose of their waste in an environmentally inappropriate manner. This fact infers the importance of adopting proper waste management practices, added to awareness through environmental education in the municipality, especially in rural communities.